Mechanisms involved in hereditary angioedema with normal C1-inhibitor activity - Shamanaev, Aleksandr; Dickeson, S. Kent; Ivanov, Ivan; Litvak, Maxim; Sun, Mao-Fu; Kumar, Sunil; Cheng, Quifang; Srivastava, Priyanka; He, Tracey Z.; Gailani, David (Frontiers in Physiology, 2023)
Patients with the inherited disorder hereditary angioedema (HAE) suffer from episodes of soft tissue swelling due to excessive bradykinin production. In most cases, dysregulation of the plasma kallikrein-kinin system due to deficiency of plasma C1 inhibitor is the underlying cause. However, at least 10% of HAE patients have normal plasma C1 inhibitor activity levels, indicating their syndrome is the result of other causes. Two mutations in plasma protease zymogens that appear causative for HAE with normal C1 inhibitor activity have been identified in multiple families. Both appear to alter protease activity in a gain-of-function manner. Lysine or arginine substitutions for threonine 309 in factor XII introduces a new protease cleavage site that results in formation of a truncated factor XII protein (-factor XII) that accelerates kallikrein-kinin system activity. A glutamic acid substitution for lysine 311 in the fibrinolytic protein plasminogen creates a consensus binding site for lysine/arginine side chains. The plasmin form of the variant plasminogen cleaves plasma kininogens to release bradykinin directly, bypassing the kallikrein-kinin system. Here we review work on the mechanisms of action of the FXII-Lys/Arg309 and Plasminogen-Glu311 variants, and discuss the clinical implications of these mechanisms.